Understanding the nature of processes: an information-processing perspective. Issue 1 (2nd February 2018) - Zelt, Sarah; Schmiedel, Theresa; vom Brocke, Jan
Abstract : Purpose: While researchers and practitioners agree on the importance to adapt business process management (BPM) practices to the nature of processes, the authors observe a lack of research on how to most meaningfully distinguish processes in order to apply context-specific BPM practices that increase process efficiency and effectiveness. The purpose of this paper is to systematically analyze the nature of processes as one contextual factor for BPM. Design/methodology/approach: Based on a literature review, the authors systematically derive process dimensions that describe the nature of processes and apply an information-processing perspective to the process level as a theoretical lens through which to analyze and structure these process dimensions. Findings: The authors identified 36 dimensions used to describe process differences that can be consolidated into five generic dimensions based on an information-processing perspective: interdependence of process participants, differentiation of process participants, process analyzability, variability, and importance. Research limitations/implications: The paper derives process dimensions from the literature and links them to extant theories as a foundation for context-sensitive BPM. The findings serve as a basis for further conceptualizing BPM and for explaining seemingly contradicting findings about whether management practices increase or decrease organizational performance. Practical implications: While the paper focuses on understanding and explaining process differences, the authors also demonstrate how these dimensions can be used to make strategic management decisions in order to increase the effectiveness and efficiency of processes. Originality/value: The authors systematically conceptualize process differences as a foundation for contingent process management. In addition, the authors demonstrate that organizational processes provide a new field of application for information-processing theory.